Research on coastline extraction and dynamic change from remote sensing images based on deep learning - Lv, Qingzhe; Wang, Qi; Song, Xiaoli; Ge, Binfu; Guan, Hao; Lu, Tongtong; Tao, Zui (Frontiers in Environmental Science, 2024)
Accurate coastline extraction is crucial for the scientific management and protection of coastal zones. Due to the diversity of ground object details and the complexity of terrain in remote sensing images, the segmentation of sea and land faces challenges such as unclear segmentation boundaries and discontinuous coastline contours. To address these issues, this study improve the accuracy and efficiency of coastline extraction by improving the DeeplabV3+ model. Specifically, this study constructs a sea-land segmentation network, DeepSA-Net, based on strip pooling and coordinate attention mechanisms. By introducing dynamic feature connections and strip pooling, the connection between different branches is enhanced, capturing a broader context. The introduction of Coordinate Attention allows the model to integrate coordinate information during feature extraction, thereby allowing the model to capture longer-distance spatial dependencies. Experimental results has shown that the model can achieves a land-sea segmentation mean Intersection over Union (mIoU) ration and Recall of over 99% on all datasets. Visual assessment results show more complete edge details of sealand segmentation, confirming the model's effectiveness in complex coastal environments. Finally, using remote sensing data from a coastal area in China as an application instance, coastline extraction and dynamic change analysis were implemented, providing new methods for the scientific management and protection of coastal zones.